Tekanan Peran, Kompleksitas Tugas, Pelatihan Auditor, dan Kesadaran Kecurangan atas Laporan Keuangan - Yefta Andi Kus Nugroho; Febriana Clarissa Bella Rambu Ngana (Perspektif Akuntansi, 2022)
This research aims to test the effect of role stress, the complexity of the task, and auditor training toward awereness of fraud against the financial statements. The data used in this research is the primary data using questionnaires that were distributed to 60 respondents. The respondents in this study was an auditor who follow Professional Training organized by the Institute of Public Accountants Indonesia. Using quantitive methods such as multiple linear regression analysis, the results suggest that (1) Role stress have no effect toward awareness of fraud (2) The complexity of the task have no effect toward awareness of fraud (3) Auditor training have positive and significant toward awareness of fraud.